Long Term (4 Years) Performance of Co/Ce Coated 441 for SOFC Interconnect Applications. (30th May 2017) - Goebel, Claudia; Berger, Robert; Lundberg, Mats W; Westlinder, Jörgen; Svensson, Jan-Erik; Froitzheim, Jan
Abstract : Co/Ce coated 441 samples were exposed at 800 °C in laboratory air for up to 37 000 h and subsequently characterized using different techniques. Mass gain data of all samples were recorded throughout exposure. Cr-evaporation measurements were conducted and compared with unexposed Co/Ce coated AISI 441 as well as unexposed and uncoated AISI 441. Furthermore SEM analysis on BIB cross-sections was performed on 7 000 h, 23 000 h and 35 000 h exposed Co/Ce coated 441.